2019
DOI: 10.3390/ph12030124
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Mechanism of the Essential Oils from Two Succulent Plants in Multidrug Resistance Leukemia Cell

Abstract: Drug resistance remains a major challenge in the treatment of cancer. The multiplicity of the drug resistance determinants raises the question about the optimal strategies to deal with them. Essential oils showed to inhibit the growth of different tumor cell types. Essential oils contain several chemical classes of compounds whose heterogeneity of active moieties can help prevent the development of drug resistance. In the present paper, we analyzed, by gas chromatography-mass spectrometry the chemical composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Analog results obtained on AML cell lines with C. juttae EO have been described for the essential oil extracted from Kalanchoe beharensis [110]. Additionally, in this case, we observed an inhibition of cell growth and an induction of cell death, depending on the inhibition of the NF-κB pathway.…”
Section: Essential Oilssupporting
confidence: 88%
See 2 more Smart Citations
“…Analog results obtained on AML cell lines with C. juttae EO have been described for the essential oil extracted from Kalanchoe beharensis [110]. Additionally, in this case, we observed an inhibition of cell growth and an induction of cell death, depending on the inhibition of the NF-κB pathway.…”
Section: Essential Oilssupporting
confidence: 88%
“…Additionally, in this case, we observed an inhibition of cell growth and an induction of cell death, depending on the inhibition of the NF-κB pathway. This EO produced a significant decrease in many targets of NF-κB both at the mRNA and protein levels, like those of P-gp, IAPs, and Bcl-2, once again confirming the central role of NF-κB in the tumorigenesis process and, above all, in determining multi-drug resistance; all this makes it a potential pharmacological target for antitumor molecules [110].…”
Section: Essential Oilsmentioning
confidence: 59%
See 1 more Smart Citation
“…This was closely related to the complex pathogenesis of tumors. However, the wide application of RNA sequencing technology facilitated the study of the mechanism of anti-tumor drugs [49]. RNA sequencing is currently the preferred technology for gene expression analysis, and it could quickly and accurately detect the differences of gene expression among different groups [50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works demonstrated that essential oils (EOs), from succulent plants, have antitumor activities on different types of tumors such as triple negative breast cancer and acute myeloid leukemia all characterized by scarce responsiveness to chemotherapeutic drugs [ 5 , 6 , 7 ]. The biological effects showed that the EOs extracted by the hydrodistillation of leaves seem to be due to the presence of terpene compounds such as phytol.…”
Section: Introductionmentioning
confidence: 99%